2014
DOI: 10.4134/bkms.2014.51.4.949
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Ternary Cyclotomic Polynomials

Abstract: Abstract. Let Φn(x) = φ(n) k=0 a(n, k)x k denote the n-th cyclotomic polynomial. In this note, let p < q < r be odd primes, where q ≡ 1 (mod p) and r ≡ −2 (mod pq), we construct an explicit k such that a(pqr, k) = −2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Kaplan (2007) [64, Lemma 1] proved the following lemma, which provides a formula for the coefficients of ternary cyclotomic polynomials. This is known as Kaplan's lemma and has been used to prove several results on ternary cyclotomic polynomials [37,48,49,51,60,89,100,101,102,105,106]. Lemma 3.1 (Kaplan's lemma).…”
Section: Ternary Cyclotomic Polynomialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaplan (2007) [64, Lemma 1] proved the following lemma, which provides a formula for the coefficients of ternary cyclotomic polynomials. This is known as Kaplan's lemma and has been used to prove several results on ternary cyclotomic polynomials [37,48,49,51,60,89,100,101,102,105,106]. Lemma 3.1 (Kaplan's lemma).…”
Section: Ternary Cyclotomic Polynomialsmentioning
confidence: 99%
“…[103] also showed that if p ≡ 1 (mod w), q ≡ 1 (mod pw), and r ≡ w (mod pq), for some integer w ≥ 2, then A + (pqr) = 1. Furthermore, for q ≡ 1 (mod p) and r ≡ −2 (mod pq), Zhang (2014) [100] constructed an explicit j such that a pqr (j) = −2, so that Φ pqr (X) is not flat. Regarding nonflat ternary cyclotomic polynomials with small heights, Zhang (2017) [101] showed that for every prime p ≡ 1 (mod 3) there exist infinitely many q and r such that A(pqr) = 3.…”
Section: Flatnessmentioning
confidence: 99%
“…Without fixing p, the first infinite family of ternary cyclotomic polynomials Φ pqr (x) with height exactly 2 was given by Elder [7], which showed that if q ≡ 1 (mod p) and r ≡ ±2 (mod pq), then A(pqr) = 2 (see Zhang [15] for another proof of this result).…”
Section: B Zhangmentioning
confidence: 99%